2015
DOI: 10.1523/jneurosci.4246-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

New Whole-Body Sensory-Motor Gradients Revealed Using Phase-Locked Analysis and Verified Using Multivoxel Pattern Analysis and Functional Connectivity

Abstract: Topographic organization is one of the main principles of organization in the human brain. Specifically, whole-brain topographic mapping using spectral analysis is responsible for one of the greatest advances in vision research. Thus, it is intriguing that although topography is a key feature also in the motor system, whole-body somatosensory-motor mapping using spectral analysis has not been conducted in humans outside M1/SMA. Here, using this method, we were able to map a homunculus in the globus pallidus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 50 publications
10
75
0
Order By: Relevance
“…These neighboring representations may thus more easily remap onto the deprived hand region, and consequently, projections from the putamen hand representation to its cerebral/cerebellar counterparts would appear as remapping that is independent of the cerebral/cerebellar somatotopic layouts. This hypothesis is consistent with anatomical evidence for a closed-loop, reciprocal circuit between primary sensorimotor cortex, cerebellum and basal ganglia, such that each terminal projects to and receives inputs from each other terminal, with varying somatotopic layouts within each terminal (Nambu, 2011;Dum et al, 2014;Zeharia et al, 2015). As our findings reveal remapping in all three of these interconnected terminals, it is plausible that the documented remapping is initiated by the basal ganglia, or further upstream.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These neighboring representations may thus more easily remap onto the deprived hand region, and consequently, projections from the putamen hand representation to its cerebral/cerebellar counterparts would appear as remapping that is independent of the cerebral/cerebellar somatotopic layouts. This hypothesis is consistent with anatomical evidence for a closed-loop, reciprocal circuit between primary sensorimotor cortex, cerebellum and basal ganglia, such that each terminal projects to and receives inputs from each other terminal, with varying somatotopic layouts within each terminal (Nambu, 2011;Dum et al, 2014;Zeharia et al, 2015). As our findings reveal remapping in all three of these interconnected terminals, it is plausible that the documented remapping is initiated by the basal ganglia, or further upstream.…”
Section: Discussionsupporting
confidence: 88%
“…Similar controversy regarding the role of somatotopic boundaries in shaping remapping also exists in amputation research. In adult amputees, remapping is commonly attributed to residual arm representation (Kew et al, 1994;Irlbacher et al, 2002;Raffin et al, 2016); (but see Gagne et al, 2011;Makin et al, 2013b) and mouth representation (Flor et al, 1995;Elbert et al, 1997;Karl et al, 2001;Lotze et al, 2001;MacIver et al, 2008;Foell et al, 2014); (though see Makin et al, 2013a;Makin et al, 2015;Raffin et al, 2016), both thought to neighbor the hand region (though see Zeharia et al, 2015;Roux et al, 2018; as well as hand and lip regions in Figure 4). More recent findings reveal remapping of the intact hand representation into the deprived cortex (Bogdanov et al, 2012;Makin et al, 2013b;Philip and Frey, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A functional localiser to independently identify digitselective regions of interest was also conducted before the active task. This localiser was also organised into digit-specific blocks over two scans, but with a set inter-digit sequence design (travelling wave, also known as phaseencoding design; Kikkert et al, 2016;Kolasinski et al, 2016;Mancini, Haggard, Iannetti, Longo, & Sereno, 2012;Sanchez-Panchuelo et al, 2010;Wandell, Dumoulin, & Brewer, 2007;Zeharia, Hertz, Flash, & Amedi, 2015).…”
Section: General Procedurementioning
confidence: 99%
“…This type of organization has been observed in the human sensorimotor cortex: blood oxygen level-dependent (BOLD) signals of V1 voxels shown to predict signals in V3 voxels at similar locations in the retinotopic map than those at dissimilar locations [Heinzle et al, 2011]. In the auditory [Cha et al, 2014] and somatosensory cortices [Zeharia et al, 2015, Cauda et al, 2011], corresponding regions in the right and left hemispheres with similar representations (tonotopic and somatotopic representation) are functionally connected. However, such topographical preservation of connectivity has not been widely observed in the association areas, even though smooth gradients of representation have previously been observed in one association area—the TPJ [Huth, 2016].…”
Section: Introductionmentioning
confidence: 94%
“…Functional connectivity patterns have been often investigated by measuring the correlation of activity of brain regions during a resting-state task [Heinzle et al, 2011, Cha et al, 2014, Zeharia et al, 2015, Cauda et al, 2011, Koch et al, 2002, Hagmann et al, 2008, Honey et al, 2009, Tao et al, 2015]. Recent studies have demonstrated that tasks such as viewing movies produce more reliable identification of functional connectivity patterns than resting-state conditions [Vanderwal et al, 2017, Finn et al, 2017, Wang et al, 2017].…”
Section: Introductionmentioning
confidence: 99%